Analysis of the frequency of maxillary sinus pathology among male and female adults - Cherkes, M.; Student, V.; Masna, Z.; Ivasivka, K.; Rudnytska, Kh. (Journal of Education, Health and Sport, 2021)
The maxillary sinuses diseases are an actual clinical problem today. The aim of our study was to determine the frequency of pathology of the maxillary sinuses of different origin and its age dynamics in adults. 500 series of anonymized tomograms of adults were analyzed: 22-35 years (1st group) and 36-60 years (2nd group in men) and 36-55 years (2nd group in women). Cone-beam computed tomography (CT) of the nose, paranasal sinuses, and upper jaw was performed on a Point 3D Combi 500 cone-beam tomograph. RealScan software was used to analyze the test results. The results of the study showed that among the adults who applied for examination of the maxillary sinus, only 20% had no pathology. Patients of the first age group are most often diagnosed with pathological changes of the maxillary sinus, which have a rhinogenic origin. In persons of the second age group, regardless of gender, the pathology of the maxillary sinus of odontogenic origin is most often diagnosed. With age, the number of pathologies of odontogenic origin increase both in men and in women, and the number of pathologies of other origin, including rhinogenic - decreases.